Sztuka osób z niepełnosprawnością intelektualną jako strefa kontaktu - Pawelczak, Katarzyna (Studia Edukacyjne, 2025)
Art uses the human need to understand and be impressed, to wonder and at the same time come to terms with ambiguity (Magsamen, Ross, 2023). When something moves, or “gets to us”, we become interested in the author and the context; we want to get to know more. The point of experiencing art is that we learn a specific way of being, being mindful (Gadamer, 1993) and encountering a perspective other than our own. According to Jean Dubuffet, Art Brut is art created outside the mainstream culture, often by excluded or marginalized people. In this context, the work of people with intellectual disabilities becomes a special contact zone, or a place where the worlds of the artist, the recipient, and society meet. This art has the potential to break stereotypes, update ways of thinking, and build new and inclusive social relationships.